Brazilian donkey slaughter and exports from 2002 to 2019 - Mariana Bombo Perozzi Gameiro; Vanessa Theodoro Rezende; Adroaldo José Zanella (Brazilian Journal of Veterinary Research and Animal Science, 2021)
The international demand for donkeys has increased sharply in recent years, motivated by China’s growing interest in producing ejiao (a traditional medicine made from donkey skin) and, in a smaller proportion, donkey meat. Since the Chinese donkey population dropped by 75.4% in the past 25 years, the country has searched for supply in the international market, mainly in Africa and South America. Aiming to understand the participation of Brazil in this scenario, this paper presents and discusses official data on donkey slaughter and donkey meat and skin exports in Brazil from 2002 to 2019. After the recent news reports of donkey trade-related mistreatment in the Brazilian Northeast, the issue has attracted attention from public authorities, the media, and civil society, but it lacked a quantitative description that could give a tangible dimension to the situation. The interpretation of these data is made with the collaboration of qualitative research methods, emphasizing some aspects of human-animal relations.